Food policy liberalization in Bangladesh: how the government and the markets delivered - Chowdhury, Nuimuddin; Farid, Nasir; Roy, Devesh (International Food Policy Research Institute, 2006)
Three factors, advent of new technology (HYV), development of infrastructure and market liberalization working in tandem have delivered favorable food security outcomes for Bangladesh. Bangladesh’s food-policy has benefited from a liberalized trade regime and a consistent downsizing of the government, all with favorable effects on poverty and nutrition. Post liberalization, the findings suggest a perceptible increase in the cost-effectiveness of the public food grain distribution system (PFDS). The favorable effects of liberalization are also evident in growths in outputs, market size, the size of private stocks, the emergence of a two peak harvest seasonality, and finally in declining real rice prices. The government has moreover downsized the PFDS, making poverty-reduction a priority basis for grain allocation. While imports relative to total availability have remained virtually unchanged during the last 25 years, public issue relative to the availability has fallen by about a half. Average food grain consumption has fallen slightly during the 1990s but in face of rising incomes, this could partly be driven by diversifying tastes. Comparing the efficiency of the private and the public sector, the private marketing margin is slightly higher. In spite of the significant advantage(s) enjoyed by the public sector, the margin being thin is significant. In order to account for the expected global changes under the Doha round, simulations using competitive spatial-equilibrium models for the world’s rice and wheat markets forecast increase in prices for rice and wheat by 21.7% and 10.1% respectively by 2013. USDA global CGE models (2001) show figures of increase in wheat prices by 18.1%, and rice prices by 10.1%. These estimates are used in a multi-market model for Bangladesh as estimates for global price shocks. Sensitivity analysis shows that over a range of values involving both an upper and a lower limit, small declines will occur in real incomes and caloric levels of both urban poor and rural landless households, while large farms will experience a small gain in their real incomes. Based on values corresponding to the lower limit, overall effects on food security are however quite small.